Rural paradigms and governance models in the LEADER Programme: case studies from North Karelia (Finland) and South Tyrol (Italy) - Rizzo, Fulvio (2011)
Because of a variety of postmodern developments, throughout the 20th century the Westphalian state changed in many ways. New structures between state-like forms, civil society organizations, and private market actors have emerged, resulting in a hybrid combination between both government and governance, and sectoral and integrated policies. The interaction between LEADER partnerships and the broader regionalization and regionalism contexts represents an important contribution to the understanding of different rural paradigms and their associated governance models. This paper investigates the key actors and how their power relations are structured in two LEADER Local Action Groups, one located in North Karelia (Finland) and the other in South Tyrol (Italy). The empirical data collected confirms the current struggle between the old and new rural paradigms, which is occurring from the local to the transnational scale. Furthermore, the investigation of this comparison suggests that the introduction of new governing structures has taken different forms in the rural context; as such, they have to be verifi ed in the light of geographical contingencies. Aufgrund einer Vielzahl postmoderner Entwicklungen veränderte sich das Bundesland Westfalen im 20. Jahrhundert auf vielfältige Weise. Zwischen staatsähnlichen Formen, zivilgesellschaftlichen Organisationen und privatwirtschaftlichen Akteuren entstanden neue Strukturen, die zu einer Hybridkombination von Regierung und Governance sowie von sektoralen und integrierten Politiken führen. Die Interaktion zwischen LEADER-Partnerschaften und dem breiteren Kontext von Regionalisierung und Regionalismus ist ein wichtiger Beitrag zum Verständnis verschiedener Paradigmen des ländlichen Raumes und der damit verbundenen Governance-Modelle. Dieser Artikel untersucht die Hauptakteure in zwei lokalen LEADER-Aktionsgruppen (die eine befindet sich in Nordkarelien, Finnland und die andere in Südtirol, Italien) und legt dar, wie deren Machtverhältnisse strukturiert sind. Die erhobenen ...